2014
DOI: 10.1101/007203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concerning RNA-Guided Gene Drives for the Alteration of Wild Populations

Abstract: Gene drives may be capable of addressing ecological problems by altering entire populations of wild organisms, but their use has remained largely theoretical due to technical constraints. Here we consider the potential for RNA-guided gene drives based on the CRISPR nuclease Cas9 to serve as a general method for spreading altered traits through wild populations over many generations. We detail likely capabilities, discuss limitations, and provide novel precautionary strategies to control the spread of gene driv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
388
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(392 citation statements)
references
References 113 publications
(199 reference statements)
0
388
0
4
Order By: Relevance
“…Unlike previous technologies, CRISPR-Cas9 offers simplicity, flexibility, and precision in gene targeting, such that any standard molecular biology laboratory could adopt the technology with little additional specialist equipment or training (7). Perhaps most importantly, CRISPR-Cas9 is efficient and inexpensive compared with all previously proposed gene drive technologies (4).…”
Section: Driven To Extinctionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike previous technologies, CRISPR-Cas9 offers simplicity, flexibility, and precision in gene targeting, such that any standard molecular biology laboratory could adopt the technology with little additional specialist equipment or training (7). Perhaps most importantly, CRISPR-Cas9 is efficient and inexpensive compared with all previously proposed gene drive technologies (4).…”
Section: Driven To Extinctionmentioning
confidence: 99%
“…When included as part of a gene drive, a CRISPR-Cas9-generated mutation will make copies of itself anywhere the genome sequence is complementary to the gRNA (7), and hence will convert individuals heterozygous for the mutation into homozygotes (4). Unlike previous technologies, CRISPR-Cas9 offers simplicity, flexibility, and precision in gene targeting, such that any standard molecular biology laboratory could adopt the technology with little additional specialist equipment or training (7).…”
Section: Driven To Extinctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Church and Kevin Esvelt, of Harvard's Wyss Institute for Biologically Inspired Engineering, have suggested that one could use CRISPR/Cas9 to modify an entire population of wild organisms (10). A prime target: mosquitoes that carry pathogens such as the malaria parasite.…”
mentioning
confidence: 99%